Division And Combination In Linear Algebra - Fang, Liang; Chena, Rui (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper, the relationship between matrix operation, linear equations, linear representation of vector groups and linear correlation is discussed, and the idea of division and combination in linear algebra is discussed to help learners understand the connections between various knowledge points of linear algebra from multiple angles, deep levels, and high dimensions.